2023
DOI: 10.3389/fmicb.2023.1147846
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated colistin resistance among human clinical Enterobacterales isolates: national surveillance in the Czech Republic

Abstract: The occurrence of colistin resistance has increased rapidly among Enterobacterales around the world. We performed a national survey of plasmid-mediated colistin resistance in human clinical isolates through a retrospective analysis of samples from 2009 to 2017 and a prospective sampling in 2018–2020. The aim of this study was to identify and characterize isolates with mcr genes from various regions of the Czech Republic using whole genome sequencing (WGS). Of all 1932 colistin-resistant isolates analyzed, 73 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Several mcr-1 -associated STs including ST744, ST10, and ST162 also alarmingly overlap between livestock and clinical settings ( 51 , 52 ). We observed this phenomenon while comparing the data from our study and another project of our team that was focused on human patients in the Czech Republic ( 19 ). Despite no detection of a clonal pair of isolates with meat and human origin, we detected closely related isolates with a minimum of 38 SNPs in case of ST1011.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Several mcr-1 -associated STs including ST744, ST10, and ST162 also alarmingly overlap between livestock and clinical settings ( 51 , 52 ). We observed this phenomenon while comparing the data from our study and another project of our team that was focused on human patients in the Czech Republic ( 19 ). Despite no detection of a clonal pair of isolates with meat and human origin, we detected closely related isolates with a minimum of 38 SNPs in case of ST1011.…”
Section: Discussionmentioning
confidence: 67%
“…We compared our data with mcr- carrying E. coli strains coming from Czech patients sampled during 2010–2020 ( 19 ). We observed that several STs overlapped with our study including ST69, ST88, ST131, ST162, ST744, and ST1011 (Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of colistin as an antibiotic of last resort is greatly threatened by its overuse and the associated rise of plasmid-borne mobile colistin resistance genes [ 50 , 51 , 52 ], spreading rapidly via horizontal gene transfer [ 53 ]. Resistance to colistin is generated by the chromosomally mediated modification of lipopolysaccharide (LPS) [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is important in Bangladesh, given extensive colistin-resistant Escherichia coli in broiler meat and chicken feces [39][40][41] exacerbating resistance among patients to colistin in Bangladesh [42][43][44][45]. Over-the-counter dispensing of antibiotics is also common in Bangladesh and is a concern, especially when this involves 'Reserve' antibiotics [46][47][48][49] The use of colistin as an antibiotic of last resort is greatly threatened by its overuse and the associated rise of plasmid-borne mobile colistin resistance genes [50][51][52], spreading rapidly via horizontal gene transfer [53]. Resistance to colistin is generated by the chromosomally mediated modification of lipopolysaccharide (LPS) [54].…”
Section: Introductionmentioning
confidence: 99%